Organic hydrogel and preparation method thereof
By introducing MXene nanosheets and specific polymers into organic hydrogels, a network structure with hydrogen bonds and uniform dispersion is formed, which solves the problem of insufficient electromagnetic interference shielding ability and environmental stability, and realizes electromagnetic at low temperatures Shielding performance and mechanical flexibility, suitable for wearable electronics.
Patent Information
- Application Number
- CN202411389550.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
Organic hydrogels have shortcomings in electromagnetic interference shielding capabilities and have poor environmental stability, especially at low temperatures, and their performance will be affected.
Using an organic hydrogel containing MXene nanosheets, polymers derived from phenol and aprone-based monomers, and crosslinking agents, the MXene nanosheets are constructed by forming hydrogen bonds and uniformly dispersing MXene nanosheets, combined with the filling of organic solvents and water. Mesh structure to improve mechanical properties and electromagnetic shielding capabilities.
It achieves good electromagnetic shielding performance and mechanical flexibility at low temperatures, and organic hydrogels exhibit excellent adhesion and environmental adaptability when adhering to various matrix surfaces, and is suitable for wearable electronic devices.
Smart Images

Figure CN119264319A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of flexible wearable electronic device materials, and specifically relates to an organic hydrogel and a preparation method thereof. Background Art
[0002] Organic hydrogel refers to a 3D polymer network prepared by partially replacing the water in the hydrogel with an organic solvent. Compared with hydrogel, although the environmental stability of organic hydrogel is improved, its electromagnetic interference shielding ability still needs to be improved. Summary of the invention
[0003] The following is a summary of the subject matter described in detail in this application. This overview is not intended to limit the scope of protection of this application.
[0004] The purpose of the embodiments of the present application is to provide an organic hydrogel and a preparation method thereof. The specific technical scheme is as follows:
[0005] The first aspect of the present application is to provide an organic hydrogel having a network structure; the network structure includes MXene nanosheets, a first polymer and a second polymer, the first polymer includes a structural unit derived from a phenol-based monomer, and the second polymer includes a structural unit derived from an acrylic monomer; at least one of the first polymer and the second polymer forms a hydrogen bond with the above-mentioned MXene nanosheet; the above-mentioned organic hydrogel also includes an organic solvent and water, and the organic solvent and water are filled in the above-mentioned network structure.
[0006] In some embodiments, hydrogen bonds are formed between the first polymer and the second polymer.
[0007] In some embodiments, the phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols.
[0008] In some embodiments, the mass percentage of the first polymer in the organohydrogel is 2% to 6%.
[0009] In some embodiments, the acrylic monomer includes any one or more of acrylic acid, C1-C3 alkyl-substituted acrylic acid, acrylamide, and C1-C3 alkyl-substituted acrylamide.
[0010] In some embodiments, the organohydrogel further comprises a cross-linking agent.
[0011] In some embodiments, the cross-linking agent includes N,N-methylenebisacrylamide.
[0012] In some embodiments, the single layer thickness of the MXene nanosheet is 1 nm to 2 nm, and the multilayer thickness is 5 nm to 10 nm.
[0013] In some embodiments, the material of the MXene nanosheets includes any one or more of Ti3AlC2, Ti2AlC, Nb2AlC, Ti3C2, Ti2C, Ta4C3, Nb2C, V2C, and Mo2C.
[0014] In some embodiments, the mass percentage content of the MXene nanosheets in the organic hydrogel is 0.3% to 2%.
[0015] In some embodiments, the organohydrogel further comprises a metal salt.
[0016] In some embodiments, the metal salt includes any one or more of ferric chloride, cobalt nitrate, nickel nitrate or hydrates thereof.
[0017] In some embodiments, the mass percentage of the metal salt in the organic hydrogel is 0.5% to 2%.
[0018] In some embodiments, the organic solvent includes any one or more of ethylene glycol (EG), glycerol (Gly), and sorbitol.
[0019] In some embodiments, the mass percentage of the organic solvent in the organohydrogel is 15% to 35%.
[0020] In some embodiments, the mass percentage of the water in the organohydrogel is 35% to 60%.
[0021] The second aspect of the present application is to provide a method for preparing the organohydrogel described in the first aspect, the preparation method comprising the following preparation process:
[0022] preparing a dispersion containing MXene nanosheets;
[0023] Preparation of hydrogel: mixing the above dispersion, phenol monomer, acrylic monomer and cross-linking agent to form a hydrogel;
[0024] Preparation of organic hydrogel: immersing the above hydrogel in a mixed solvent to obtain the organic hydrogel; the mixed solvent includes an organic solvent and water.
[0025] In some embodiments, preparing the hydrogel comprises:
[0026] Prepare a mixed solution of phenol monomers: disperse the metal salt in water, add the phenol monomers, and mix well to form a mixed solution;
[0027] Polymerization reaction: under ice bath conditions, add the above dispersion, acrylic monomer and crosslinking agent to the above mixed solution, stir evenly, then add oxidant and react to obtain hydrogel.
[0028] In some embodiments, the mass ratio of the metal salt to the catechol monomer is 1:(1-20).
[0029] In some embodiments, the mass ratio of the phenol-based monomer to the acrylic-based monomer is (5-20):(75-90).
[0030] In some embodiments, the mass ratio between the phenol monomer and the cross-linking agent is (5-20): (0.1-1).
[0031] In some embodiments, the mass ratio of the oxidant to the phenol monomer is (1.5-2.5):(5-20).
[0032] In some embodiments, the oxidizing agent comprises persulfate.
[0033] In some embodiments, the volume ratio between the organic solvent and water in the mixed solvent is 1:(1-4).
[0034] The organic hydrogel provided in the present application has good application prospects in deformable wearable electronic devices. This is because the organic hydrogel provided in the present application has mechanical flexibility and conductivity, and high environmental stability. It can be adhered to the surface of various substrates to make wearable strain or pressure sensors, and has broad application prospects in health monitoring, electronic skin, human-computer interaction, artificial intelligence and other fields.
[0035] The beneficial effects of the technical solution disclosed in this application are mainly reflected in the following:
[0036] The organic hydrogel provided in the present application has mechanical flexibility and electrical conductivity, and high environmental stability, which is mainly manifested in that its electrical conductivity changes little after being placed for a period of time, and the organic hydrogel can still exhibit the same electromagnetic shielding ability at low temperatures as at room temperature. In addition, the organic hydrogel is also convenient to attach to the surface of various substrates to form flexible wearable electronic devices, so the organic hydrogel has relatively good application prospects in the fields of wearable strain or pressure sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application. The accompanying drawings are only used to illustrate the preferred implementation methods and do not constitute a limitation on the technical solution of the present application. In addition, the same reference numerals are used throughout the accompanying drawings to represent the same components.
[0038] In the attached picture:
[0039] Figure 1The X-ray diffraction patterns of MXene powder and MXene nanosheets of some embodiments of the present application;
[0040] Figure 2 The scanning electron microscope images of the organohydrogels of some embodiments of the present application;
[0041] Figure 3 , Figure 4 , Figure 5 and Figure 6 This is a performance test graph of the organohydrogel of some embodiments of this application. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is further described below in conjunction with the accompanying drawings and specific embodiments. The embodiments in the present application can be implemented in a plurality of different forms. A person of ordinary skill in the art can easily understand the fact that the implementation and content can be transformed into various forms without departing from the purpose and scope of the present application. Therefore, the present application should not be interpreted as being limited to the contents described in the following embodiments. In the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined arbitrarily with each other.
[0043] In the context of the present application, when a layer / element is referred to as being "on" another layer / element, the layer / element may be directly on the other layer / element or an intervening layer / element may exist between them. In addition, if a layer / element is "on" another layer / element in one orientation, the layer / element may be "under" the other layer / element when the orientation is reversed.
[0044] In the description of the present application, ordinal numbers such as "first" and "second" are provided to avoid confusion among constituent elements rather than to limit the quantity.
[0045] In this specification, for the sake of convenience, the words and phrases indicating the orientation or positional relationship, such as "middle", "upper", "lower", "front", "back", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., are used to illustrate the positional relationship of the constituent elements with reference to the drawings. This is only for the purpose of facilitating the description of this specification and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on this application. The positional relationship of the constituent elements is appropriately changed according to the direction in which each constituent element is described. Therefore, it is not limited to the words and phrases described in the specification, and can be appropriately replaced according to the situation.
[0046] In this specification, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate, or the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0047] “A and / or B” includes the following two combinations: A only, B only, and a combination of A and B.
[0048] “At least one of A, B, and C” has the same meaning as “at least one of A, B, or C” and both include the following combinations of A, B, and C: A only, B only, C only, the combination of A and B, the combination of A and C, the combination of B and C, and the combination of A, B, and C.
[0049] Exemplary embodiments are described herein with reference to cross-sectional views and / or plan views that are idealized exemplary drawings. In the drawings, the thickness of layers and regions are exaggerated for clarity. Therefore, variations in shape relative to the drawings due to, for example, manufacturing techniques and / or tolerances are conceivable. Therefore, the exemplary embodiments should not be interpreted as being limited to the shapes of the regions shown herein, but include shape deviations due to, for example, manufacturing. For example, an etched region shown as a rectangle will typically have curved features. Therefore, the regions shown in the drawings are schematic in nature, and their shapes are not intended to illustrate the actual shape of regions of the device, and are not intended to limit the scope of the exemplary embodiments.
[0050] Hydrogel is a 3D polymer network that can swell in water. The polymer network is solid, while the water phase of the hydrogel enables the carrier to diffuse rapidly, indicating that the hydrogel has liquid-like transport properties. The water in the hydrogel network can produce strong polarization losses to attenuate GHz electromagnetic waves and transmit current through ions in the water phase.
[0051] Organic hydrogel refers to a 3D polymer network prepared by partially replacing the water in the hydrogel with an organic solvent. Compared with hydrogel, although the environmental stability of organic hydrogel is improved, its electromagnetic interference shielding ability still needs to be improved.
[0052] In order to solve the above technical problems, the first aspect of the present application is to provide an organic hydrogel, which has a network structure; the network structure includes MXene nanosheets, a first polymer and a second polymer, the first polymer includes a structural unit derived from a phenol-based monomer, and the second polymer includes a structural unit derived from an acrylic monomer; at least one of the first polymer and the second polymer forms a hydrogen bond with the MXene nanosheet, and the above organic hydrogel also includes an organic solvent and water, and the organic solvent and water are filled in the above network structure.
[0053] The MXene nanosheets in the present application refer to two-dimensional materials containing at least one of transition metal carbides, nitrides or carbonitrides, which have a large specific surface area and relatively abundant edge catalytic active sites. At the same time, the surface of the MXene nanosheets is modified with at least one functional group including -OH, =O, -NH2, F, etc., which makes it easy to form intramolecular or intermolecular hydrogen bonds between MXene nanosheets and between MXene nanosheets and other compounds containing the above functional groups.
[0054] As described above, the MXene nanosheets of the present application are easy to form intramolecular or intermolecular hydrogen bonds, making the MXene nanosheets easy to agglomerate. At least one of the first polymer and the second polymer provided by the present application is easy to form hydrogen bonds with the MXene nanosheets, which is conducive to alleviating the agglomeration phenomenon, and effectively improving the dispersion of the MXene nanosheets, so that the MXene nanosheets show stable anti-electromagnetic interference capabilities, and is also conducive to improving the mechanical properties of the organic hydrogel. At the same time, the structural unit derived from the phenol monomer in the first polymer itself has adhesion, so that the organic hydrogel also has a certain adhesion strength, and the organic hydrogel is easily adhered to the surface of various substrates (such as natural polymer materials or synthetic polymer materials, etc.) to make various devices. In addition, the organic solvent and water filled in the mesh structure make the organic hydrogel have high electromagnetic interference shielding performance while also obtaining excellent environmental adaptability, such as still having relatively good electromagnetic interference shielding performance even in low temperature environments.
[0055] Therefore, the organic hydrogel provided by the present application exhibits stable anti-electromagnetic interference capability and good mechanical properties.
[0056] In some embodiments, hydrogen bonds are formed between the first polymer and the second polymer.
[0057] The hydrogen bonds formed between the first polymer and the second polymer of the present invention are beneficial to further improving the mechanical properties of the organohydrogel.
[0058] In some embodiments, the phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols.
[0059] The phenol monomers listed in the present application contain two or more -OH groups on their respective benzene rings, which enables the formed first polymer to better form hydrogen bonds with the MXene nanosheets.
[0060] In some embodiments, the mass percentage of the first polymer in the organic hydrogel is 2% to 6%.
[0061] The present application controls the mass percentage content of the first polymer in the above-mentioned organic hydrogel to be 2% to 6%, which is conducive to better dispersion of MXene nanosheets.
[0062] In these embodiments, the present application discloses that the mass percentage content of the first polymer in the above-mentioned organic hydrogel is any one of 2%, 2.6%, 3%, 3.8%, 4%, 4.5%, 4.6%, 5%, 6% or any one of the values satisfying the above-mentioned range.
[0063] In some embodiments, the acrylic monomer includes any one or more of acrylic acid, C1-C3 alkyl-substituted acrylic acid, acrylamide, and C1-C3 alkyl-substituted acrylamide.
[0064] In the present application, C1~C3 alkyl substituted acrylic acid includes any one or more of methacrylic acid, ethacrylic acid, n-propyl acrylic acid, and isopropyl acrylic acid. Similarly, C1~C3 alkyl substituted acrylamide includes any one or more of methacrylamide, ethacrylamide, n-propyl acrylamide, and isopropyl acrylamide.
[0065] The types of acrylic monomers listed in this application all contain functional groups that are easy to form hydrogen bonds. On the one hand, the formed second polymer can better disperse the MXene nanosheets, and on the other hand, hydrogen bonding forces are generated between the second polymer and the first polymer to improve the mechanical properties of the organic hydrogel.
[0066] In some embodiments, the above-mentioned organic hydrogel further comprises a crosslinking agent. The crosslinking agent of the present application is conducive to forming a crosslinked polymer with the first polymer and the second polymer, and the crosslinked polymer is conducive to the uniform dispersion of the MXene nanosheets and the improvement of the mechanical properties of the organic hydrogel. The type of the crosslinking agent of the present application is any conventional type in the art.
[0067] In some embodiments, the cross-linking agent includes N,N-methylenebisacrylamide. In the specific embodiments of the present application, N,N-methylenebisacrylamide is mainly used as an example for explanation, but the present application does not exclude other types of cross-linking agents.
[0068] In some embodiments, the single layer thickness of the MXene nanosheet is 1 nm to 2 nm, and the multilayer thickness is 5 nm to 10 nm.
[0069] The thickness of the MXene nanosheets of the present application may be measured by observation using a scanning electron microscope, and the specific measurement or observation method may include any conventional method in the art.
[0070] The single-layer thickness of the MXene nanosheet in this application refers to the thickness of a single sheet layer, and the multi-layer thickness refers to the thickness of more than two layers.
[0071] In some embodiments, the material of the above-mentioned MXene nanosheets includes any one or more of Ti3AlC2, Ti2AlC, Nb2AlC, Ti3C2, Ti2C, Ta4C3, Nb2C, V2C, and Mo2C.
[0072] In some embodiments, the mass percentage content of the above-mentioned MXene nanosheets in the above-mentioned organic hydrogel is 0.3% to 2%.
[0073] The MXene nanosheets of the present application have a thickness of nanometers and a width of micrometers, and are relatively easy to agglomerate. The use of the first polymer and the second polymer in the present application is conducive to reducing the agglomeration of the MXene nanosheets and improving the effect of uniform dispersion.
[0074] In these embodiments, the mass percentage content of the above-mentioned MXene nanosheets in the above-mentioned organic hydrogel is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any one of the above-mentioned range values.
[0075] In some embodiments, the organohydrogel further comprises a metal salt.
[0076] In some embodiments, the metal salt includes any one or more of ferric chloride, cobalt nitrate, nickel nitrate or hydrates thereof.
[0077] In some embodiments, the weight percentage of the metal salt in the organic hydrogel is 0.5% to 2%.
[0078] The metal salt of the present application is beneficial to further adjust the mechanical flexibility of the organohydrogel.
[0079] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned metal salt in the above-mentioned organic hydrogel is any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any one of the values satisfying the above-mentioned range.
[0080] In some embodiments, the organic solvent includes any one or more of ethylene glycol (EG), glycerol (Gly), and sorbitol.
[0081] In some embodiments, the mass percentage of the organic solvent in the organic hydrogel is 15% to 35%.
[0082] In some embodiments, the mass percentage of the water in the organohydrogel is 35% to 60%.
[0083] The water in the organic hydrogel of the present application can produce strong polarization losses to attenuate electromagnetic waves and transmit current through ions in the water phase. However, due to poor environmental stability, hydrogel shielding materials with pure water as the dispersion medium will suffer from the problems of water evaporation and freezing below zero degrees, and affect the anti-electromagnetic shielding ability of the hydrogel. Using organic solvents to replace part of the water to prepare organic hydrogels can effectively improve the environmental stability of the gel, but the electromagnetic interference shielding ability of this type of organic hydrogel decreases with the decrease of water content. How to obtain excellent environmental adaptability while maintaining high electromagnetic interference shielding performance is a difficult problem that needs to be solved urgently for organic hydrogels. The present application can achieve excellent environmental adaptability while taking into account high electromagnetic interference shielding performance by reasonably controlling the amount of the two.
[0084] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned organic solvent in the above-mentioned organic hydrogel is 15%, 15.7%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 23.8%, 24%, 25%, 26%, 27%, 27.7%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any one of the values satisfying the above-mentioned range.
[0085] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned water in the above-mentioned organic hydrogel is 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% or any one of the values satisfying the above-mentioned range.
[0086] The second aspect of the present application is to provide a method for preparing an organohydrogel, which comprises the following preparation process:
[0087] preparing a dispersion containing MXene nanosheets;
[0088] Preparation of hydrogel: mixing the above dispersion, phenol monomer, acrylic monomer and crosslinking agent to form hydrogel, wherein the phenol monomer is polymerized to form a first polymer, the acrylic monomer is polymerized to form a second polymer, and the first polymer and the second polymer are further crosslinked under the action of the crosslinking agent;
[0089] Preparation of organic hydrogel: immersing the hydrogel in a mixed solvent to obtain the organic hydrogel; the mixed solvent includes an organic solvent and water.
[0090] In some embodiments, preparing the hydrogel comprises:
[0091] Prepare a mixed solution of phenol monomers: disperse the metal salt in water, add the phenol monomers, and mix well to form a mixed solution;
[0092] Polymerization reaction: under ice bath conditions, add the above dispersion, acrylic monomer and crosslinking agent to the above mixed solution, stir evenly, then add oxidant and react to obtain hydrogel.
[0093] In some embodiments, the mass ratio of the metal salt to the catechol monomer is 1:(1-20).
[0094] The present application discloses in these embodiments that the mass ratio between the above-mentioned metal salt and the above-mentioned catechol monomer is any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or any one of the values satisfying the above-mentioned ranges.
[0095] In some embodiments, the mass ratio of the phenol-based monomer to the acrylic-based monomer is (5-20):(75-90).
[0096] The present application controls the amount of the phenol monomer and the acryl monomer to better disperse the MXene nanosheets.
[0097] In these embodiments, the present application discloses that the mass ratio between the phenol monomer and the above-mentioned acrylic monomer is any one of 5:75, 5:85, 5:90, 10:75, 10:85, 10:90, 20:75, 20:85, 20:90 or any one of the above-mentioned range values. In some embodiments, the mass ratio between the above-mentioned phenol monomer and the above-mentioned cross-linking agent is (5-20): (0.1-1).
[0098] In these embodiments, the present application discloses that the mass ratio between the phenol monomer and the cross-linking agent is any one of 5:0.1, 5:0.5, 5:1, 10:0.1, 10:0.5, 10:1, 20:0.1, 20:0.5, 20:1 or any one of the above ranges. In some embodiments, the mass ratio between the oxidant and the phenol monomer is (1.5-2.5): (5-20).
[0099] In these embodiments, the present application discloses that the mass ratio between the oxidant and the above-mentioned phenol monomer is any one of 1.5:5, 2:5, 2.5:5, 1.5:10, 2:10, 2.5:10, 1.5:20, 2:20, 2.5:20 or any one of the above-mentioned range values.
[0100] In some embodiments, the oxidizing agent comprises a persulfate.
[0101] In some embodiments, the volume ratio of the organic solvent to water is 1:(1-4).
[0102] The present application discloses in these embodiments that the volume ratio between the organic solvent and water is any one of 1:1, 1:2, 1:3, 1:4 or any one of the values within the above ranges.
[0103] In some embodiments, the present application provides a specific preparation process of the organohydrogel, including the following preparation steps:
[0104] S1. Prepare a dispersion containing MXene nanosheets: stir and mix lithium fluoride and concentrated hydrochloric acid, then add MXene powder, stir at 30°C to 40°C for 10h to 40h to perform an etching reaction. After washing with deionized water, perform ultrasonic treatment under argon flow for 1h to 5h, and finally centrifuge the dispersion to collect the supernatant, which is the dispersion of MXene nanosheets;
[0105] S2. Preparation of MXene-containing hydrogel:
[0106] Dissolve the metal salt (metal ion catalyst) in deionized water, then add catechol monomer and stir for 1 to 5 minutes to form a catechol-metal ion solution. Add the MXene dispersion, acrylic monomer and crosslinker to the catechol-metal ion solution in an ice bath. After stirring for 1 to 5 minutes, add an aqueous solution of an oxidant to prepare a hydrogel electrolyte MH.
[0107] S3. Preparation of MXene-containing organic hydrogel:
[0108] The MXene organic hydrogel is prepared by a solvent replacement method. The MXene hydrogel is immersed in a mixed solution of an organic solvent and water at room temperature for 1 h to 3 h to prepare the MXene organic hydrogel.
[0109] In some embodiments, the concentration of lithium fluoride is 0.05 g / mL to 0.10 g / mL.
[0110] In some embodiments, the concentration of concentrated hydrochloric acid is 7 mol / L to 9 mol / L.
[0111] In some embodiments, the dispersion is prepared at a concentration of 0.3 g / mL to 0.6 g / mL.
[0112] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0113] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0114] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0115] MXene powder: 200 mesh powder from achem-block. Other chemicals were purchased from Anergy as analytical grade chemicals.
[0116] Example 1-1
[0117] A method for preparing an organohydrogel is provided, the method comprising the following steps:
[0118] Dissolve 1.0g lithium fluoride LiF in 10mL 9mol / L concentrated hydrochloric acid and stir to mix, then add 0.5g 400 mesh Ti3AlC2 powder. Stir at 35℃ for 24h to perform etching reaction. After washing with deionized water, perform ultrasonication for 2h under argon flow. Finally, centrifuge the dispersion and collect the supernatant. Among them, the single layer thickness of MXene nanosheets is 1.5nm, and the multilayer thickness is 5nm.
[0119] Dissolve 0.10g of ferric chloride hexahydrate in 4mL of deionized water, then add 0.50g of dopamine hydrochloride (DA) and stir for 2 minutes to form a DA-iron ion solution. Under ice bath conditions, a dispersion containing 0.30g of MXene, 2.49g of acrylic acid (AA), and 0.01g of N, N'-methylenebisacrylamide (BIS) were added to the DA-iron ion solution, and the solution was filled to 6mL with water. After stirring for 2 minutes, 1mL of an aqueous solution containing 0.2g / mL ammonium persulfate was added and stirring was continued to obtain the hydrogel MH1.
[0120] The hydrogel MH1 was immersed in 50 mL of a mixed solution of ethylene glycol and water in a volume ratio of 1:4 at room temperature for 1 h to prepare the organic hydrogel MO1.
[0121] Example 1-2
[0122] A method for preparing an organohydrogel is provided, the method comprising the following steps:
[0123] Dissolve 0.8g lithium fluoride LiF in 10mL 8mol / L concentrated hydrochloric acid and stir to mix, then add 0.5g 400 mesh Ti3AlC2 powder. Stir at 35℃ for 24h to perform etching reaction. After washing with deionized water, perform ultrasonication for 2h under argon flow. Finally, centrifuge the dispersion and collect the supernatant.
[0124] 0.20g of cobalt nitrate hexahydrate was dissolved in 4mL of deionized water, followed by the addition of 0.40g of tannic acid (TA) and stirring for 2 minutes to form a TA-cobalt ion solution. Under ice bath conditions, a dispersion containing 0.40g of MXene, 2.59g of acrylic acid (AA), and 0.01g of N, N'-methylenebisacrylamide (BIS) were added to the TA-cobalt ion solution, and the solution was filled to 6mL with water. After stirring for 2 minutes, 1mL of an aqueous solution containing 0.2g / mL of ammonium persulfate was added and stirring was continued to obtain the hydrogel MH2.
[0125] The hydrogel MH2 was immersed in 50 mL of a mixed solution of glycerol and water in a volume ratio of 1:2 at room temperature for 1 h to prepare the organic hydrogel MO2.
[0126] Examples 1-3
[0127] A method for preparing an organohydrogel is provided, the method comprising the following steps:
[0128] Dissolve 0.5g lithium fluoride LiF in 10mL 7mol / L concentrated hydrochloric acid and stir to mix, then add 0.5g 400 mesh Ti3AlC2 powder. Stir at 35℃ for 24h to perform etching reaction. After washing with deionized water, perform ultrasonic treatment for 2h under argon flow. Finally, centrifuge the dispersion and collect the supernatant.
[0129] 0.30g of nickel nitrate hexahydrate was dissolved in 4mL of deionized water, followed by the addition of 0.30g of tea polyphenols (TP) and stirring for 2 minutes to form a TP-nickel ion solution. Under ice bath conditions, a dispersion containing 0.45g of MXene, 2.69g of acrylic acid (AA), and 0.02g of N, N'-methylenebisacrylamide (BIS) were added to the TP-nickel ion solution, and the solution was filled to 6mL with water. After stirring for 2 minutes, 1mL of an aqueous solution containing 0.2g / mL of ammonium persulfate was added and stirring was continued to obtain the hydrogel MH3.
[0130] The hydrogel MH3 was immersed in 50 mL of a mixed solution of sorbitol and water in a volume ratio of 1:1 at room temperature for 1 h to prepare the organic hydrogel MO3.
[0131] Examples 1-4
[0132] A method for preparing an organic hydrogel is provided. The method is different from that in Example 1 in that acrylic acid is replaced by methacrylic acid.
[0133] Dissolve 1.0g lithium fluoride LiF in 10ml 9mol / L concentrated hydrochloric acid and stir to mix, then add 0.5g 400 mesh Ti3AlC2 powder. Stir at 35℃ for 24h to carry out etching reaction. After washing with deionized water, perform ultrasonic treatment for 2h under argon flow. Finally, centrifuge the dispersion and collect the supernatant.
[0134] Dissolve 0.10g of ferric chloride hexahydrate in 4ml of deionized water, then add 0.50g of dopamine hydrochloride (DA) and stir for 2 minutes to form a DA-iron ion solution. Under ice bath conditions, add a dispersion containing 0.30g of MXene, 2.97g of methacrylic acid (mAA), and 0.01g of N, N'-methylenebisacrylamide (BIS) to the DA-iron ion solution, and fill the solution to 6ml with water. After stirring for 2 minutes, add 1mL of an aqueous solution containing 0.2g / ml ammonium persulfate and continue stirring to obtain hydrogel MH4.
[0135] The hydrogel MH4 was immersed in 50 ml of a mixed solution of ethylene glycol and water in a volume ratio of 1:4 at room temperature for 1 h to prepare the organic hydrogel MO4.
[0136] Examples 1-5
[0137] A method for preparing an organic hydrogel is provided. The method is different from that in Example 1 in that the hydrogel MH1 is immersed in a mixed solution of 50 mL of ethylene glycol and water in a volume ratio of 1:2 at room temperature for 1 hour to prepare the organic hydrogel MO1a.
[0138] Example 2-1
[0139] A method for preparing an organic hydrogel is provided. The method is different from that in Example 1 in that 0.23 g of dopamine hydrochloride is added, and the rest of the method is the same as in Example 1.
[0140] Example 2-2
[0141] A method for preparing an organic hydrogel is provided. The method is different from that in Example 1 in that 0.65 g of dopamine hydrochloride is added, and the rest is the same as in Example 1.
[0142] Comparative Example 1
[0143] A method for preparing an organic hydrogel is provided. The method is different from that in Example 1 in that no catechol monomer is added.
[0144] Dissolve 1.0g lithium fluoride LiF in 10ml 9mol / L concentrated hydrochloric acid and stir to mix, then add 0.5g 400 mesh Ti3AlC2 powder. Stir at 35℃ for 24h to carry out etching reaction. After washing with deionized water, perform ultrasonic treatment for 2h under argon flow. Finally, centrifuge the dispersion and collect the supernatant.
[0145] Under ice bath conditions, 2.99 g of acrylic acid (AA) and 0.01 g of N,N'-methylenebisacrylamide (BIS) were added to a dispersion solution containing 0.30 g of MXene, and the solution was filled to 6 mL with water. After stirring for 2 minutes, 1 ml of an aqueous solution containing 0.2 g / ml of ammonium persulfate was added, and stirring was continued to obtain the hydrogel MH0.
[0146] The above hydrogel MH0 was immersed in 50 ml of a mixed solution of ethylene glycol and water in a volume ratio of 1:4 at room temperature for 1 h to prepare the organic hydrogel MO0.
[0147] The contents of the main raw materials in the above examples and comparative examples are shown in the following table.
[0148] Table 1 List of main raw materials and ingredients
[0149]
[0150]
[0151] [Characterization]:
[0152] (1) X-ray diffraction: The DMAXD-2500PC X-ray diffractometer from Rigaku, Japan, was used to perform in-situ measurements of MXene powder (MAX) and MXene nanosheets in the dispersion.
[0153] The XRD patterns of the MXene powder (MAX) of Example 1-1 and the MXene nanosheets in the dispersion are obtained, as shown in FIG. Figure 1 As shown, the XRD spectrum of the MXene nanosheet is at 5.81°, the interlayer distance increases, and it increases by 1.73nm compared with the powder, and no diffraction peak of the MXene powder is detected, which indicates that the MXene nanosheet is successfully exfoliated using the design method provided in this application, and the single layer thickness of the MXene nanosheet is 1.5nm. In Example 1-1, this application mainly uses Ti3AlC2 material as an example to illustrate the dispersion of the first polymer and the second polymer on the MXene nanosheet, but in fact, other types of MXene nanosheets listed in this application are also applicable to this application, and this application will not be repeated here.
[0154] (2) Scanning electron microscopy: The internal structure of the organohydrogel was observed using a JSM6390 scanning electron microscope from JEOL, Japan. The gel sample was freeze-dried first. The freeze-dried sample was then cut open to observe the internal structure. Before SEM observation, the sample surface was sprayed with gold.
[0155] The scanning electron microscope (SEM) images of Example 1-1 and Example 1-3 were obtained. Figure 2 , Figure 2 A is Example 1-1, Figure 2 B is Example 1-3. Combined with the figure, it can be seen that after freeze-drying the obtained organic hydrogel, a scanning electron microscope was used to take a cross-section photo. It can be seen that MXene did not agglomerate in the gel, and the gel network became denser with the increase of MXene content. It is proved that the MXene nanosheets with unique two-dimensional layered structure have surface-bonded free radicals, which can serve as physical crosslinking points to enhance the stability of the network.
[0156] [Performance Test]:
[0157] ① Stress-strain capacity of organic hydrogel: The tensile test was conducted using a 5567 universal testing machine from Instron, USA. The loading rate was 120 mm / min. The width of the sample was 25 mm, the thickness was 3 mm, and the distance between the clamps was 5 mm.
[0158] The stress-strain curves of the organohydrogels of Examples 1-1 to 1-3 were obtained, and the Figure 3 It can be seen that with the increase of MXene content, the mechanical strength of the organic hydrogel increases significantly.
[0159] ② Conductivity of organic hydrogel: The conductivity of porous materials was characterized using the Tonghui TH26011CS test system. The test fixture and wires were connected to the material to be tested through conductive silver glue, and the material was tested using the four-point method.
[0160] The conductivity change of the organohydrogel of Example 1-1 within 7 days was obtained, and the conductivity of the organohydrogel of Example 1-1 was obtained. Figure 4 It can be seen that although the organic hydrogel is exposed to the air for a long time, the conductivity of MO1 decreases by less than 5%, which shows that the water retention capacity of the organic hydrogel designed in the present application far exceeds that of ordinary hydrogels.
[0161] ③ Electromagnetic shielding ability of organic hydrogel: Agilent's N5244A vector network analyzer is used to test the material through the waveguide method. The material is cut to a fixed size and placed in the waveguide cavity. The two sides of the waveguide cavity are tightly connected to the two ports of the vector network analyzer and then measured after being tightly fixed.
[0162] The electromagnetic shielding performance of the organohydrogel of Example 1-2 at 25°C and -25°C is as follows: Figure 5 Hint.
[0163] ④ Adhesion ability of organic hydrogel: an organic hydrogel sample with an area of 25 mm*20 mm was glued between two glass substrates to be tested, and then the sample was stretched to failure at a loading rate of 5 mm / min using a 5567 universal testing machine from Instron, USA.
[0164] The adhesion ability of the organohydrogels of the above embodiments and comparative examples on smooth surfaces was obtained. Figure 6 It can be seen that the bisphenol structure provides the gel with good bonding properties, and with the increase of bisphenol monomer content, the bonding properties of the gel are significantly improved.
[0165] According to the above test method, the performance table of each embodiment is shown as follows:
[0166] Table 2 Performance list
[0167]
[0168]
[0169] It can be seen from the above embodiments that the organic hydrogel provided in the present application has mechanical flexibility and conductivity, and has high environmental stability. It can still exhibit the same electromagnetic shielding ability at low temperatures as at normal temperatures; in addition, due to its strong adhesion, it is also convenient to attach to the surface of various substrates to form deformable wearable electronic devices.
[0170] It should be understood that the terms used herein are only for the purpose of describing specific example embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "an" and "said" as used herein may also be meant to include plural forms. The terms "include", "comprise", "contain", and "have" are inclusive and therefore indicate the presence of the stated features, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, steps, operations, elements, parts, and / or combinations thereof. The method steps, processes, and operations described herein are not interpreted as requiring them to be performed in the specific order described or illustrated, unless the execution order is clearly indicated. It should also be understood that additional or alternative steps may be used. The above is only a preferred specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or replacements that can be easily thought of by a technician familiar with the technical field within the technical scope disclosed in the present application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the scope of protection of the claims.
Claims
1. An organohydrogel, characterized in that: The organic hydrogel has a network structure; The network structure includes MXene nanosheets, a first polymer and a second polymer; The first polymer includes structural units derived from phenolic monomers; The second polymer includes structural units derived from acryl-based monomers; A hydrogen bond is formed between at least one of the first polymer and the second polymer and the MXene nanosheet; The organohydrogel further comprises an organic solvent and water, and the organic solvent and water are filled in the network structure.
2. The organohydrogel according to claim 1, characterized in that: A hydrogen bond is formed between the first polymer and the second polymer.
3. The organohydrogel according to claim 2, characterized in that: The phenol monomers include any one or more of dopamine, tannic acid, and tea polyphenols; and / or; The acrylic monomer includes any one or more of acrylic acid, C1-C3 alkyl substituted acrylic acid, acrylamide, and C1-C3 alkyl substituted acrylamide.
4. The organohydrogel according to any one of claims 1 to 3, characterized in that: The mass percentage content of the first polymer in the organic hydrogel is 2% to 6%.
5. The organohydrogel according to any one of claims 1 to 3, characterized in that: The single layer thickness of the MXene nanosheet is 1nm to 2nm, and the multilayer thickness is 5nm to 10nm; and / or; The material of the MXene nanosheets includes any one or more of Ti3AlC2, Ti2AlC, Nb2AlC, Ti3C2, Ti2C, Ta4C3, Nb2C, V2C, and Mo2C; and / or; The mass percentage content of the MXene nanosheets in the organic hydrogel is 0.3% to 2%.
6. The organohydrogel according to any one of claims 1 to 3, characterized in that: The organic solvent includes any one or more of ethylene glycol, glycerol, and sorbitol; and / or; The mass percentage of the organic solvent in the organic hydrogel is 15% to 35%; and / or; The mass percentage of water in the organic hydrogel is 35% to 60%.
7. The organohydrogel according to any one of claims 1 to 3, characterized in that: The organohydrogel further comprises a cross-linking agent; The cross-linking agent includes N,N-methylenebisacrylamide.
8. The organohydrogel according to any one of claims 1 to 3, characterized in that: The organohydrogel further comprises a metal salt; The metal salt includes any one or more of ferric chloride, cobalt nitrate, nickel nitrate or hydrates thereof.
9. A method for preparing the organohydrogel according to any one of claims 1 to 8, characterized in that: The preparation process includes the following: preparing a dispersion containing MXene nanosheets; Preparing a hydrogel: mixing the dispersion, phenol monomer, acrylic monomer and cross-linking agent to form a hydrogel; Preparation of organic hydrogel: immersing the hydrogel in a mixed solvent to obtain the organic hydrogel; the mixed solvent includes an organic solvent and water.
10. The preparation method according to claim 9, characterized in that: The preparation of the hydrogel comprises: Prepare a mixed solution of phenol monomers: disperse the metal salt in water, add the phenol monomers, and mix well to form a mixed solution; Polymerization reaction: under ice bath conditions, the dispersion, acrylic monomer and cross-linking agent are added to the mixed solution, stirred evenly, and then an oxidant is added to react to obtain a hydrogel.
11. The preparation method according to claim 10, characterized in that: The mass ratio between the metal salt and the phenol monomer is 1:(1-20); and / or; The mass ratio of the phenolic monomer to the acrylic monomer is (5-20): (75-90); and / or; The mass ratio of the phenol monomer to the cross-linking agent is (5-20): (0.1-1).
12. The preparation method according to any one of claims 10 to 11, characterized in that: The mass ratio of the oxidant to the phenol monomer is (1.5-2.5): (5-20); and / or; The oxidizing agent includes a persulfate.
13. The preparation method according to claim 9, characterized in that: The volume ratio between the organic solvent and water is 1:(1-4).